Thermostable DNA polymerase chain amplification of t(14;18) chromosome breakpoints and detection of minimal residual disease. - Crescenzi, M (1988)
Achieving the capacity to detect minimal numbers of neoplastic cells is a major cancer diagnostic challenge. Chromosomal translocations such as the t(14;18)(q32;q21) found in follicular and some nonfollicular lymphomas provide a tumor-specific molecular marker. The 14;18 breakpoints are focused at one of six immunoglobulin heavy chain joining (JH) regions on chromosome 14 and a small major breakpoint region (MBR) of the BCL2 gene on chromosome 18. We utilized universal oligonucleotide primers of a region 5' to the BCL2 MBR and at the 3' end of JH segments to initiate a DNA polymerase chain reaction that amplified these BCL2-JH junctures. Use of thermostable DNA polymerase enabled annealing and synthesis steps at temperatures approaching the melting point of the primers, providing a sensitive and specific assay capable of detecting 1 lymphoma cell in 10(6) normal cells. This technique identified the subclinical presence of leukemic cells in all seven patients examined, including two in clinical remission. It also assessed the effectiveness of protocols designed to purge malignant cells from marrow. Moreover, this approach enabled the rapid DNA sequencing of chromosomal breakpoints without their molecular cloning. This assay markedly refines the capacity to detect minimal residual disease and should improve the ability to determine the stage of disease, stratify treatment, and evaluate therapy.